2021
DOI: 10.1177/09603271211045955
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic exposure and non-carcinogenic health effects

Abstract: Inorganic arsenic (iAs) exposure is a serious health problem that affects more than 140 million individuals worldwide, mainly, through contaminated drinking water. Acute iAs poisoning produces several symptoms such as nausea, vomiting, abdominal pain, and severe diarrhea, whereas prolonged iAs exposure increased the risk of several malignant disorders such as lung, urinary tract, and skin tumors. Another sensitive endpoint less described of chronic iAs exposure are the non-malignant health effects in hepatic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 280 publications
(461 reference statements)
0
16
0
Order By: Relevance
“…Cadmium exposure was also not associated with either birth length (0.01; 95% CI, 0.04 to 0.02; n = 11) or birth head circumference (0.02; 95% CI, 0.06 to 0.02; n = 8), according to a meta-analysis conducted by Khoshhali et al [ 64 ], and supported by Flannery et al [ 39 ]. Their scoping review suggested no relationship with birth length because most studies eligible for their review found no statistically significant relationship, namely, six out of seven studies measuring fetal cadmium exposure and seven out of eleven studies measuring maternal cadmium exposure.…”
Section: Effects Of Non-essential Trace Elements On Pregnancy Outcomesmentioning
confidence: 82%
See 1 more Smart Citation
“…Cadmium exposure was also not associated with either birth length (0.01; 95% CI, 0.04 to 0.02; n = 11) or birth head circumference (0.02; 95% CI, 0.06 to 0.02; n = 8), according to a meta-analysis conducted by Khoshhali et al [ 64 ], and supported by Flannery et al [ 39 ]. Their scoping review suggested no relationship with birth length because most studies eligible for their review found no statistically significant relationship, namely, six out of seven studies measuring fetal cadmium exposure and seven out of eleven studies measuring maternal cadmium exposure.…”
Section: Effects Of Non-essential Trace Elements On Pregnancy Outcomesmentioning
confidence: 82%
“…Humans are primarily exposed to arsenic through drinking water, as well as through food [ 34 , 37 ]. Arsenic exposure has been associated with short- and long-term health effects such as cardiovascular diseases, adverse effects on the immune system and respiratory infections [ 37 , 38 , 39 ], and several cancer types [ 37 , 38 , 40 ]. Suggested mechanisms include the induction of oxidative stress and inflammation [ 37 , 39 ], as well as genomic instability and epigenetic regulation [ 38 , 40 ].…”
Section: Prenatal Exposure To Non-essential (Toxic) Trace Elementsmentioning
confidence: 99%
“…Inorganic arsenic is highly toxic, exhibiting carcinogenic and non-carcinogenic effects. Chronic exposure to arsenic causes severe health issues, including but not limited to skin damages, cardiovascular disease, diabetes, neurological disfunctions, and multiple types of cancer [ 49 , 50 , 51 ]. In addition, studies showed that in utero and early childhood exposure has significant negative impacts on cognitive development [ 52 ].…”
Section: Epitranscriptomic Mechanisms Of Metal Toxicity and Carcinoge...mentioning
confidence: 99%
“…The liver is the most important target organ of arsenic metabolism [3]. Epidemiological studies linked chronic iAs exposure to an increased risk of liver disease, fibrosis, cirrhosis, and liver carcinogenesis [4][5][6]. The mechanisms underlying arsenic-Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s).…”
Section: Introductionmentioning
confidence: 99%